Communication works - Gamble, Teri Kwal; Gamble, Michael , 1943- (McGraw-Hill, 2010)
Presents communication principles, interpersonal communication, group communication, and public speaking in an interactive manner. Recognizing the challenges that our world presents for the communication students of the 21st century, this title includes ESL coverage and coverage of ethical, cultural, and technological issues.